MR venography of the human brain using susceptibility weighted imaging at very high field strength. - Koopmans, P; Manniesing, R; Niessen, W; Viergever, M; Barth, M (2008)
OBJECTIVE: We investigate the implications of high magnetic field strength on MR venography based on susceptibility-weighted imaging (SWI) and estimate the optimum echo time to obtain maximum contrast between blood and brain tissue. MATERIALS AND METHODS: We measured tissue contrast and T2* relaxation times at 7 T of gray matter, white matter, and venous blood in vivo. RESULTS: T2* relaxation times of gray matter, white matter, and venous blood in vivo yielded 32.9 +/- 2.3, 27.7 +/- 4.3, and 7.4 +/- 1.4 ms, respectively. Optimum TE was found to be 15 ms which is supported by theoretical considerations. Using this optimum TE, we acquired 3D high resolution datasets with a large volume coverage in a short measurement time that show very detailed microanatomical structures of the human brain such as intracortical veins and laminar cortical substructures. CONCLUSIONS: By applying optimised vessel filters (vesselness filter and vessel enhancing diffusion) whole brain MR venograms can be obtained at 7 T with a significantly reduced measurement time compared to 3 T.